Healthcare professionals’ views about delivering a rehabilitation programme for individuals living with Atrial Fibrillation: a cross – sectional survey - Munyra Alhotye; Rachael Evans; Andre Ng; Sally J. Singh (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background People living with Atrial Fibrillation (AF) often experience symptoms such as irregular heartbeat, shortness of breath, and fatigue, which can significantly limit their physical activity and overall quality of life. The existing approach to managing AF predominantly revolves around medication and medical procedures, and no prescription of tailored rehabilitation program (RP) is currently offered for this population. Aims This study aims to gauge the perspectives of healthcare professionals regarding the implementation of a personalised RP for individuals living with AF and to identify the barriers hindering the referral process. Methods A cross-sectional online survey was conducted among healthcare professionals in the UK responsible for caring for adults with AF. The survey consisted of twelve questions designed to uncover healthcare professionals' views on RP for individuals with AF. Results A total of 209 respondents participated in the survey, with 57% being female and 43% identifying as specialist arrhythmia nurses. A significant majority (61%) of the participants expressed agreement that an RP could help individuals with AF regain their ability to carry out daily activities, and 58% believed that RP could effectively alleviate symptoms such as breathlessness and palpitations (52%). Virtually all respondents (99%) recommended that a tailored program should encompass education about AF, weight management, and symptom control (94%). Notably, the primary factor influencing their decision to make a referral was the low physical activity levels (80%). Transportation emerged as the chief obstacle to referring patients to the program (62%). A substantial majority (79%) favoured a home-based rehabilitation program as the optimal mean of delivery. Conclusions The responses from healthcare professionals reflect a keen interest in implementing a program tailored to individuals with AF, with patients' low physical activity levels being the primary motivator for referrals. Home-based rehabilitation was the preferred mode of delivery, followed by digital interventions.